External Factors of Delay that Affect the Performance of International Construction Contractors in Kuwait - Hamouda, Ahmed Atif Hussein (International Journal of Sustainable Construction Engineering and Technology, 2021)
As the construction industry in Kuwait develops, the need for international contractors to handle and manage these projects rises as well. Currently, 70% of the projects in Kuwait get delayed, some by internal factors, and some by external ones. Thus, the purpose of this research is to provide a framework for international construction contractors in Kuwait regarding the external factors of delay that they might face in their projects. External factors of delay are a newly generated type of delays that represent all the delays that are beyond the contractor’s control and cannot be anticipated in the project. In this research, the most important and frequently occurring external factors of delay were extracted and discussed with 15 project management professionals to elaborate their perspectives and construct a survey to evaluate the impact and frequency of these delaying factors in the construction industry in Kuwait. This survey was distributed to 80 project management practitioners; then, the outcomes were analyzed by using the Relative Importance Index methodology to rank the effect of the examined delaying factors. Hence this research will provide international construction contractors with an illustration of the delaying factors that they should focus on and the ones they can pay less attention to them.